(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The complexity of production processes in machine-building enterprises, high-precision technological operations, and continuous work schedules increase the relevance of hygienic requirements for workplace illumination levels. Insufficient or improperly organized lighting has been scientifically proven to cause visual analyzer strain, decreased work productivity, increased occupational injuries, and the development of occupational diseases. This literature review systematically analyzes international and national scientific sources, regulatory documents, and statistical data concerning the hygienic assessment of illumination levels at main workstations in machine-building enterprises. The results indicate that hygienically proper design of artificial and combined lighting systems is an important factor in ensuring occupational safety and improving production efficiency.